Divine Justice and Social Inequality: A Theological Response from Islamic Tradition - Marah, Thomas Sheku (Kalam Al Gazali: Education and Islamic Studies Journal, 2025)
This article examines the fundamental concept of divine justice (‘Adl) through Islamic theological perspectives and its  relevance for addressing current social inequalities. Modern societies encounter major economic disparities and systemic social neglect and injustice which  demands new theological solutions to these crises. The research uses qualitative literature review methods to analyze classical and modern  divine justice interpretations from Al-Ghazālī, Ibn Taymiyyah, Sayyid  Qutb, Kamali, Esack, and Ramadan. The Findings shows divine justice functions beyond theoretical  abstraction to establish normative guidelines which affect policy decisions, ethical principles, governance systems and human development programs. specifically, it reveals that  Islamic theology provides a unified ethical system which addresses poverty reduction alongside gender equality and social justice promotion. The practical implication of this study is that Islamic  theology serves as a transformative tool for ethical progress and societal change in modern times through its critical reinterpretation.